(untitled) (Bangladesh Agronomy Journal, 2019)
An experiment was conducted at farmer’s field of Dashpara village of Sylhet Sadar upazila during 2016-2017 to find out nutritional status of the leaves of four local and four exotic lines of sweet potato. d. The lines and variety were Local-1, Local-2, Local-5, Local-8, Exotic-1, Exotic-2, Exotic-3, Exotic-4 and BARI SP-4.The experiment was conducted by in a Randomized Complete Block Design. Crude protein, crude fat, crude fiber, total ash, moisture and carbohydrate were determined by proximate analysis whereas elemental nutrients, total sugar, starch, vitamin C, phenolic compounds and tannins were determined by the procedure outlined by Association of Analytical Chemists’ (AOAC). Ninety days old fresh leaves were collected from the experimental field for chemical analysis. Results revealed that the highest percent of carbohydrate (by difference), crude protein, crude fat, total ash and energy were in Exotic-2 (65.47), Local-2 (26.59), Local-5 (3.63), BARI SP-4 (8.35) and Local-1 (370.4 Kcal 100 g-1), respectively. The highest percent of crude fiber, total sugar and starch were recorded in Local-8 (17.79), Local-2 (5.63) and Local-8 (36.42), respectively. The Local-1 contained the highest amount of phenolic compounds and tannins while vitamin C was in Local-5 and Local-8. It was also observed that sweet potato leaves of Local-1, Local-5 and Local-8 contained appreciable levels of iron, zinc, calcium, magnesium, potassium and phosphorus. It can be concluded that the leaves of Local-1, Local-5, Local-8, Exotic-1 and Exotic-2 could be suitable for vegetables and can be included as supplement our daily nutrient requirements. Bangladesh Agron. J. 2018, 21(2): 49-58